The role of microbiota-gut-brain axis in neuropsychiatric and neurological disorders - Socała, Katarzyna; Doboszewska, Urszula; Szopa, Aleksandra; Serefko, Anna; Włodarczyk, Marcin; Zielińska, Anna; Poleszak, Ewa; Fichna, Jakub; Wlaź, Piotr (Pharmacological research, 2021)
Emerging evidence indicates that the gut microbiota play a crucial role in the bidirectional communication between the gut and the brain suggesting that the gut microbes may shape neural development, modulate neurotransmission and affect behavior, and thereby contribute to the pathogenesis and/or progression of many neurodevelopmental, neuropsychiatric, and neurological conditions. This review summarizes recent data on the role of microbiota-gut-brain axis in the pathophysiology of neuropsychiatric and neurological disorders including depression, anxiety, schizophrenia, autism spectrum disorders, Parkinson’s disease, migraine, and epilepsy. Also, the involvement of microbiota in gut disorders co-existing with neuropsychiatric conditions is highlighted. We discuss data from both in vivo preclinical experiments and clinical reports including: (1) studies in germ-free animals, (2) studies exploring the gut microbiota composition in animal models of diseases or in humans, (3) studies evaluating the effects of probiotic, prebiotic or antibiotic treatment as well as (4) the effects of fecal microbiota transplantation. [Display omitted]